PENGARUH PROMOSI MEDIA SOSIAL, KUALITAS PELAYANAN DAN LAYANAN COD TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA UD AFITA HANDCRAFT DI BONDOWOSO - Wulandasari, Hamseh; Soeliha, Siti; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of social media promotion, service quality, and COD services on purchasing decisions through purchase interest as an intervening variable at UD Afita Handcraft in Bondowoso. The research method used a quantitative approach with simple random sampling techniques on 83 respondents. The data were analyzed using Partial Least Square (PLS) through the Smart PLS 3.0 application. The results indicate that social media promotion has a positive but insignificant effect on purchase intention, while service quality and COD services have a significant positive effect. Meanwhile, service quality is proven to have a significant effect on purchasing decisions, but social media promotion and COD services do not show a significant effect. Purchase intention as an intervening variable is also proven to have a significant effect on purchasing decisions. Specifically, COD services have a significant influence on purchasing decisions through purchase interest, while social media promotions and service quality are not significant in this relationship. The implications of this study suggest that UD Afita Handcraft should focus more on improving service quality and optimizing COD services to strengthen consumer purchase interest and purchasing decisions. In addition, social media promotion strategies need to be improved to be more effective in attracting purchase interest.